Wacana Boikot Produk Israel di Panggung Media Nasional: Analisis Ideologis terhadap CNBC Indonesia dan SINDOnews.com - Arsya, imam (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
The boycott movement against Israeli products has become a global response to the humanitarian aggression that has occurred in Palestine. In Indonesia, this discourse has found space in mainstream media coverage such as CNBC Indonesia and SINDOnews.com. This study aims to examine how the two media frame the issue of boycotting Israeli products and to reveal the ideology hidden behind their reporting. This study uses a qualitative approach with the Norman Fairclough critical discourse analysis method that combines text analysis, discursive practices, and social practices. Data were obtained from the November 2023 edition of news that raised the issue of boycotting Israeli products on the two online media portals. Data were analyzed with a focus on the choice of diction, narrative structure, and actors highlighted. The results show that CNBC Indonesia tends to present a neutral-economistic discourse, emphasizing the impact of the boycott on market stability and trade. Meanwhile, SINDOnews.com focuses more on the dimensions of humanitarian solidarity and Islamic narratives. Both media present different ideological positions, reflecting the economic and ideological interests inherent in the media institution. This difference in narrative shows that the media is not just a conveyor of facts, but also helps shape public opinion through a certain ideological frame. The boycott discourse does not stand neutrally, but is produced and reproduced within a broader framework of interests. This study emphasizes the importance of media literacy in reading the ideological position of news reporting.